2018
DOI: 10.15446/dyna.v85n205.66658
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between the lognormal and Weibull Distributions by using multiple linear regression

Abstract: En el análisis de confiabilidad, las distribuciones Weibull y lognormal son ambas analizadas utilizando el logaritmo de los datos observados. Debido a que mientras el logaritmo de datos Weibull presenta sesgo, el logaritmo de datos lognormales es simétrico, entonces en este artículo basados en 1) los coeficientes de variación (CV), 2) en la desviación estándar del logaritmo de los datos, 3) en la posición del percentil de la media del logaritmo de los datos y 4) en dispersión acumulada del logaritmo antes y de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…between the Weibull and lognormal distribution carried out by References [32][33][34][35], revealed that each of the distributions had a peculiar application. In the final analysis, the authors could not reject the Weibull in favour of the lognormal distribution model, neither could they reject the lognormal distribution in favour of the Weibull.…”
Section: Cross-comparative Analysis Of Frequentist and Bayesian Persp...mentioning
confidence: 99%
See 2 more Smart Citations
“…between the Weibull and lognormal distribution carried out by References [32][33][34][35], revealed that each of the distributions had a peculiar application. In the final analysis, the authors could not reject the Weibull in favour of the lognormal distribution model, neither could they reject the lognormal distribution in favour of the Weibull.…”
Section: Cross-comparative Analysis Of Frequentist and Bayesian Persp...mentioning
confidence: 99%
“…While the Weibull data logarithm is skewed, the lognormal data logarithm is symmetrical. [32] used the following methods to discriminate between the distributions: the coefficients of variation (CV); the standard deviation of the data logarithms; the percentile position of the mean of the data logarithm; and the cumulated logarithm dispersion before and after the mean. The efficiency of the method was duly tested.…”
Section: Discriminating Between the Weibull And The Lognormal Distrib...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the lognormal distribution is frequently used in areas where the data tend to be right skewed, such as physics, economics, biostatistics, survival analysis, wireless communication, quality control, reliability analysis, material properties, fatigue life of materials, strength of some materials, etc. Various applications of the lognormal distribution are described in [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%